Sensitivity Optimization Of Au/ti Based-spr Sensor By Controlling Light Incident Wavelength For Gas Sensing Application - Nadhratul Huda Ahmad Khilmy; Wan Maisarah Mukhtar; Affa Rozana Abdul Rashid (Penerbit UTM Press, 2024)
Non-Indexed Publication